(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The purpose of this article is to show that religious teachings and philosophical theories determine their teachings concerning life after death or endless life in accordance with their vision of being, with their worldview and epistemological perspectives. Accordingly, the belief in the reincarnation is contrary to Islamic teachings concerning God, the universe and man. Keywords: Immortality, Hereafter Belief, Transmigration, Tanasuh, Reincarnation.